A gestão estratégica de recursos em ambientes regulamentados: um estudo nos programas de pós-graduação stricto sensu em administração - Backes, Danieli Artuzi Pes (2018)
This thesis is composed of a set of three interrelated studies, whose objective is to analyze the strategic management of the Stricto Sensu Postgraduate Programs in Administration (PPGA) through the institutional pressures received from the environment. The theoretical support is based on two strategic bases, the first being the Institutional Theory, through the approach of isomorphism, and the second, The Theory of Resources or RBV, through the application of the VRIO model. The research is a quanti-quali study, so the first two studies with secondary data were performed to give subsidy to the triangulation of data, conducted in the third study, which is a field survey. In the first study, multiple linear regression and Pearson correlation analysis were performed using the Ordinary Least Squares (OLS) method to evaluate the quantitative indicators of the PPGAs of concept 4, 5, 6 and 7 in the quadrennium 2013 to 2016, in order to identify the strategic behavior of the programs. The results showed that the evaluated programs follow a behavioral pattern to generate the results valued in the evaluation. However, some correlations have pointed out that there are PPGAs that adopt differentiated strategies or organize their resources differently from those with equivalent structures. Another finding is that at least half of the programs surveyed are managing to conduct their human resources, especially the faculty, in an efficient way to generate results, according to regulatory guidelines, especially the PPGAs of private institutions. In the second study, through the application of the Co-plot method to the data set, we propose to identify the existence of isomorphism in the PPGAs from the analysis of similar curricular structures between the programs, which presuppose the existence of a complementary structure of resources between programs. From the groups formed by the studied curricular axes, it was possible to verify the presence of mimetic isomorphism among the PPGAs, noting, however, that there is a difference of isomorphic intensity between the programs. In the third study we analyze the strategic management of resources and capacities in the PPGAs through the pressures received from the environment, government institutions and other organizations with which they are dependent. For the last study, we conducted field research, with the application of a semistructured interview script to 27 coordinators and former PPGA coordinators. In the study, we tested 11 propositions, concluding that there is standardized behavior in the field studied, motivated by regulatory forces, while there is also a strategic positioning and evidence of competitive behavior by higher ranking positions, and this positioning reflects organizational performance, which is obtained as a result of the ability to strategically manage resources. There is a special section devoted to the comparison of the three studies and other findings of the thesis, highlighting the theoretical and practical contributions of the research. In the final considerations, the contributions of the three studies to the organizational field are synthesized, emphasizing that for a PPGA to be legitimized and to obtain a superior position, it is not enough to follow the assessment questions, it is necessary to have broader and more assertive objectives that guarantee a differential in relation to the others. From the theoretical conceptual point of view, arising from the use of the two combined strategic theoretical bodies, reflections on the role of financing systems for performance-based research and its effects on organizational institutions and on the organization of the regulated organizational field are woven.